Treatment of Combined Injuries to the ACL and the MCL Complex: A Consensus Statement of the Ligament Injury Committee of the German Knee Society (DKG). Issue 11 (18th November 2021) - Guenther, Daniel; Pfeiffer, Thomas; Petersen, Wolf; Imhoff, Andreas; Herbort, Mirco; Achtnich, Andrea; Stein, Thomas; Kittl, Christoph; Schoepp, Christian; Akoto, Ralph; Höher, Jürgen; Scheffler, Sven; et al.
Background: Different indications and treatment options for combined injuries to the anterior cruciate ligament (ACL) and medial collateral ligament complex (MCL) are not clearly defined. Purpose: To perform a modified Delphi process with the Committee for Ligament Injuries of the German Knee Society (DKG) in order to structure and optimize the process of treating a combined injury to the ACL and MCL. Study Design: Consensus statement. Methods: Scientific questions and answers were created based on a comprehensive literature review using the central registers for controlled studies of Medline, Scopus, and Cochrane including the terms medial collateral ligament, anterior cruciate ligament, MCL, ACL, and outcome used in various combinations. The obtained statements passed 3 cycles of a modified Delphi process during which each was readjusted and rated according to the available evidence (grades A-E) by the members of the DKG Ligament Injuries Committee and its registered guests. Results: The majority of answers, including several questions with >1 graded answer, were evaluated as grade E (n = 16) or C (n = 10), indicating that a low level of scientific evidence was available for most of the answers. Only 5 answers were graded better than C: 3 answers with a grade of A and 2 answers with a grade of B. Only 1 answer was evaluated as grade D. An agreement of >80% (range, 83%-100%) among committee members was achieved for all statements. Conclusion: The results of this modified Delphi process offer a guideline for standardized patient care in cases of combined injuries to the ACL and MCL.